Identifying pathological myopia associated genes with GenePlexus in protein-protein interaction network - Luo, Yuanyuan; Wang, Yihan; Liu, Lin; Huang, Feiming; Lu, Shiheng; Yan, Yan (Frontiers in Genetics, 2025)
IntroductionPathological myopia, a severe form of myopia, is characterized by an extreme elongation of the eyeball, leading to various vision-threatening complications. It is broadly classified into two primary types: high myopia, which primarily involves an excessive axial length of the eye with potential for reversible vision loss, and degenerative myopia, associated with progressive and irreversible retinal damage.MethodsLeveraging data from DisGeNET, reporting 184 genes linked to high myopia and 39 genes associated with degenerative myopia, we employed the GenePlexus methodology in conjunction with screening tests to further explore the genetic landscape of pathological myopia.Results and discussionOur comprehensive analysis resulted in the discovery of 21 new genes associated with degenerative myopia and 133 genes linked to high myopia with significant confidence. Among these findings, genes such as ADCY4, a regulator of the cAMP pathway, were functionally linked to high myopia, while THBS1, involved in collagen degradation, was closely associated with the pathophysiology of degenerative myopia. These previously unreported genes play crucial roles in the underlying mechanisms of pathological myopia, thereby emphasizing the complexity and multifactorial nature of this condition. The importance of our study resides in the uncovering of new genetic associations with pathological myopia, the provision of potential biomarkers for early screening, and the identification of therapeutic targets.